MUFLIHATUL FAUZA UMKM PADA MASA COVID-19 - MUFLIHATUL FAUZA (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2022)
This study aims to describe what are the survival strategies that must be carried out, so UMKM are able to continue to survive in business, especially during the Covid-19. The technique data is literature and secondary data. The research methodology used analysis SWOT which is then described in a qualitative approach. The results showed that business during COVID-19 experienced a change in habits, from doing business that did not use telecommunications technology and media before Covid 19. Digitalize business during the COVID-19 is one of strategy to be able to maintain business, and also trends in the use of technology and telecommunications media, such as online business during the COVID-19.